2016
DOI: 10.1016/j.jss.2016.06.092
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to efficiency in robotic surgery: the resident effect

Abstract: Background Robotic surgery offers advantages over conventional operative approaches, but may also be associated with higher costs and additional risks. Analyzing surgical flow disruptions (FDs), defined as “deviations from the natural progression of an operation,” can help target training techniques and identify opportunities for improvement. Materials and methods Thirty-two Robotic Surgery operations were observed over a six-week period at one 900-bed surgical center. FDs were recorded in detail and classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…All studies observed complete surgical teams (including surgery, anaesthesia and nursing staff) with the goal of evaluating team performance through surgical workflow analysis and evaluation of disruptive events (9 studies), the relationship between team performance and technical outcomes (3 studies), the relationship between anticipation of surgical steps and team efficiency (1 study) or novel tools to rate team performance (3 studies).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies observed complete surgical teams (including surgery, anaesthesia and nursing staff) with the goal of evaluating team performance through surgical workflow analysis and evaluation of disruptive events (9 studies), the relationship between team performance and technical outcomes (3 studies), the relationship between anticipation of surgical steps and team efficiency (1 study) or novel tools to rate team performance (3 studies).…”
Section: Resultsmentioning
confidence: 99%
“…No study compared robot‐assisted techniques with other approaches. Five studies investigated robot‐assisted techniques and found that this approach to abdominal procedures increases team demands that surgical teams were not always able to address effectively, resulting in increased operating times. The identification and analysis of flow disruptions can provide an evidence base for improving the efficiency and safety of robot‐assisted procedures ( Table S1, supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One way to address the gap between what should happen in the operating room (OR) (‘work as imagined’) and what really happens in the OR (‘work as done’) (Xiao et al 2010) is through direct observation of surgical and other clinical processes (Blandford et al 2015; Guerlain et al 2005; Gurses et al 2012). In previous work, we used direct observation to explore some of the use problems, which we describe as surgical flow disruptions (FDs), associated with the da Vinci robotic surgery system, in relation to surgical context (Catchpole et al 2015) and trainee skill development (Jain et al 2016). In this sub-analysis of those data, we refine the original analysis, looking in detail at the sub-set of the data to provide more interpretive depth that will inform future approaches to the integration of the da Vinci and other robotic systems into surgical environments.…”
Section: Introductionmentioning
confidence: 99%